The overlooked individual : susceptibility to dental caries, erosive tooth wear and amelogenesis - Vieira, Alexandre Rezende (Basel, Switzerland : Karger, 2022)
Individual susceptibility to disease (i.e., one's own genetic background) is one of the three main components classically described in the etiology of dental caries. Hence, genes influence susceptibility to erosive tooth wear, dental development, and response to treatments and interventions. This publication is an up-to-date overview of individual susceptibility to dental caries, erosive tooth wear, and disturbances of dental development from different clinically relevant perspectives. One of the most recognized scientists in this field reports on recent research relating to human genetics - from general summaries to recommendations for daily clinical work and population-level interventions. This book covers all aspects of individual susceptibility to dental caries and erosive tooth wear. Several chapters deal with potential biological mechanisms, with additional ones providing a strong foundation in human genetics, and other chapters touch on efficacy of therapies and alternative concepts. This book is particularly recommended to dental medicine students, practitioners, other oral healthcare professionals, and scientists with an interest in translational research on dental caries and erosive tooth wear.
Keywords: DIENTES -- ENFERMEDADES -- ASPECTOS GENÉTICOS; CARIES DENTALES -- ASPECTOS GENÉTICOS; ABRASIÓN DENTARIA -- ASPECTOS GENÉTICOS; AMELOGENESIS IMPERFECTA -- ASPECTOS GENÉTICOS; PREDISPOSICIÓN GENETICA A LA ENFERMEDAD; ABRASIÓN DENTARIA